The association of CFAP65 with male infertility in Vietnamese individuals - Thuy Duong, Nguyen; Huu Dinh, Tran; Van Hai, Nong (Vietnam Journal of Biotechnology, 2022)
Cilia- and flagella-associated protein (CFAP) is a well-known protein family that plays a vital role in the spermatogenic process. Recently, the gene CFAP65, which encodes the cilia- and flagella- associated protein 65, has been focused on as a new candidate for male infertility. Mutations in this gene are frequently detected in patients with primary infertility, especially among cases with combined phenotypes of acrosome abnormalities and multiple morphological abnormalities of the flagella (MMAF). In addition, mice carrying both a complete knock-out of the CFAP65 gene and a CFAP65 homozygous frameshift mutation exhibited sterility with the typical phenotypes of MMAF. However, no case-control study has been performed on the relationship between polymorphisms in CFAP65 and male infertility in any population. Hence, our study aimed to investigate the correlation between the polymorphism CFAP65 rs117885048 and male infertility in a Vietnamese population comprising 207 infertile men and 217 healthy controls. As a result, the studied population followed Hardy-Weinberg equilibrium (HWE) (p> 0.05) and the frequencies of genotypes CC/CT/TT were 0.875, 0.12, and 0.003, respectively. The Chi-square test revealed no association between the polymorphism CFAP65 rs117885048 and the disease in this population (p > 0.05). To further interpret the correlation between single nucleotide polymorphisms in the CFAP65 gene and male infertility, a more comprehensive study with other polymorphisms needs to be considered.